FENOMENA THRIFTING DIKALANGAN MAHASISWA AKIBAT PERUBAHAN GAYA HIDUP MODERN - Arsa Reynal Dimas Suyanto; Sadam Khumaini Vindata; Tito Tilawah; Nindya Kartika Kusmayati (Cahaya Ilmu Bangsa, 2024)
Fenomena